Start Up Talk to Entrepreneur: Merubah Mindset Shift dari Follower Menjadi Owner - Hadi Ismanto; Vembri Aulia Rahmi; Muhammad Rosyihuddin (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This Community Service (PkM) activity was implemented in the form of an entrepreneurship seminar. This seminar strategically raised the theme "Changing the Mindset Shift from Follower to Owner", with the crucial aim of facilitating a paradigm shift in participants from mere passive consumers or followers to active and empowered business owners (owners). The implementation of PkM is based on the reality of the high unemployment rate among educated people and the urgency of global economic challenges that demand mental transformation and strengthening of practical skills. The main target group of this activity included students of entrepreneurship study programs from various universities in East Java as well as representatives of Micro, Small, and Medium Enterprises (MSMEs) operating in the Gresik area, ensuring the relevance of the material to academic and practical needs. This seminar featured two credible expert speakers in the field of entrepreneurship. The implementation method focused on interactive delivery of material, followed by a focused discussion session to maximize knowledge absorption. The results achieved showed a significant increase in understanding among participants, not only regarding the importance of instilling an entrepreneurial mindset but also mastery of practical aspects of business, including digital marketing implementation strategies and concrete steps in starting or developing a business unit. Through this intervention, PkM is expected to be able to provide a real contribution to accelerating the creation of new, innovative entrepreneurs and strengthening the sustainable entrepreneurial ecosystem in East Java